Teori Belajar Behavioristik dan Kognitif serta Penerapannya dalam Pendidikan Islam - Yusi Srihartini; St. Rahmani; Ahmad Mupahir; Riani Prihastati (At-Tadris: Journal of Islamic Education, 2026)
Learning theories play a fundamental role in shaping the direction and quality of educational processes. Among the various approaches that have developed in educational psychology, behaviorist and cognitive learning theories are considered two of the most influential perspectives. Each offers a distinct framework for understanding how learners acquire knowledge and develop learning behaviors. In the context of Islamic education, the application of learning theories cannot be separated from its normative values and objectives, which emphasize the formation of faith, moral character, and Islamic personality. This article aims to examine behaviorist and cognitive learning theories and to analyze their relevance and application within Islamic education. This study employs a qualitative approach through a literature review. The findings indicate that the behaviorist approach plays a significant role in shaping Islamic habits and discipline, while the cognitive approach contributes to the development of understanding and internalization of values. The balanced integration of these two approaches has the potential to strengthen holistic and value-oriented practices in Islamic education.